Peran Media Sosial dalam Menanamkan Nilai Anti Korupsi pada Generasi Z - Resti Aprilia; Lulu Salsabila T (Medan Resource Center, 2026)
Corruption continues to pose a pervasive challenge across social, political, and economic domains, requiring innovative preventive strategies that engage younger generations. Generation Z, characterized by high digital connectivity and active participation in online environments, represents a strategic demographic for the dissemination of anti-corruption values. This study investigates how social media functions as a medium for instilling anti-corruption values among Generation Z and examines the extent of its effectiveness in shaping attitudes and behaviors. Employing a qualitative approach through a literature review of recent scholarly works, this study analyzes patterns of digital engagement, content dissemination, and value internalization. The findings indicate that social media serves as a dynamic platform for education, advocacy campaigns, and character formation through interactive and visually engaging content. Its effectiveness, however, is contingent upon users’ digital literacy, the credibility of information sources, and the level of participatory engagement. The study argues that when strategically utilized, social media can operate as a transformative tool in fostering critical awareness and strengthening anti-corruption character among young people.